Optimalisasi Pemanfaatan Lahan Pekarangan melalui Microfarming sebagai Strategi Mewujudkan Kemandirian Pangan Berbasis Komunitas Di Desa Segala Anyar, Lombok Tengah - Jufri, Afifah Farida; Nikmatullah, Aluh; Yanuartati, Baiq Yulfia Elsadewi; Putri, Dwi Noorma; Danasari, Idiatul Fitri; Fitri; Sail, Fazila (Universitas Mataram, 2025)
Food insecurity remains a significant challenge in many rural areas, including in Segala Anyar Village, Pujut District, Central Lombok. This village is characterized by dryland farming systems that heavily rely on the rainy season, causing agricultural activities to halt during the dry season. This condition directly affects food availability and household income. Meanwhile, Segala Anyar Village has considerable yard space (home gardens) that has yet to be optimally utilized. This community engagement program aimed to optimize yard utilization through a microfarming approach as a strategy to achieve community-based food self-sufficiency. The activity was carried out from April to June 2025 using participatory and applicative methods. The participatory method was applied in identifying land potential and planning the program with local residents, while the applicative method involved hands-on training in organic home garden cultivation and growing media preparation. The results of the program indicated an increase in community knowledge and skills in managing yard space, along with the formation of a microfarming working group to support program sustainability. The microfarming approach proved to be a strategic solution for addressing food access disparities in dryland farming areas and promoting sustainable food self-sufficiency at the household and community levels